Assessment of interprofessional obstetric and midwifery care from the midwives’ perspective using the Interprofessional Collaboration Scale (ICS) - Schulz, Anja Alexandra; Wirtz, Markus Antonius (Frontiers in Psychology, 2023)
Introduction Interprofessional collaboration of physicians and midwives is essential for appropriate and safe care of pregnant and parturient women as well as their newborns. The complexity of woman-centered care settings requires the continuous exchange of information and the coordinated implementation of multi-and interprofessional care concepts. To analyze the midwives’ perspective on the multi-and interprofessional care process during pregnancy, birth and postpartum period, we aimed to adapt and psychometrically evaluate the Interprofessional Collaboration Scale (ICS). Methods The ICS (13 items) was answered by 299 midwives for (i) prenatal and postpartum care as well as (ii) perinatal care. Three items on equitable communication (EC) identified in qualitative interviews with N = 6 midwives were added as further aspects of quality in collaborative midwifery care. Confirmatory factor analysis was used to test competing theoretically hypothesized factorial model structures, including both care settings simultaneously, i.e., birth and prenatal/postpartum. Results A two-dimensional structure assuming the 13 original ICS items and the 3 items on EC as psychometric distinct item groups accounts for the data best. After deleting 5 ICS items with insufficient indicator reliability, a very good-fitting model structure was obtained for both prenatal/postpartum as well as perinatal care: χ2df = 192 = 226.35, p = 0.045, CFI = 0.991, RMSEA = 0.025 (90%CI: [0.004; 0.037]). Both the reduced ICS-R and the EC scale (standardized response mean = 0.579/1.401) indicate significantly higher interprofessional collaboration in the birth setting. Responsibility in consulting, attitudes toward obstetric care and frequency of collaboration with other professional groups proved to be associated with the ICS-R and EC scale as expected. Discussion For the adapted ICS-R and the EC scale a good construct validity could be confirmed. Thus, the scales can be recommended as a promising assessment for recording the collaboration of midwives with physicians working in obstetric care from the perspective of midwives. The instrument provides a validated assessment basis in midwifery and obstetric care to identify potentially divergent perspectives within interprofessional care teams in woman’s centered care.